Penelantaran Keluarga sebagai Landasan Perceraian Perspektif Sosiologi Hukum dan Fiqh Jinayah : Family Neglect as a Basis for Divorce: A Sociological and Fiqh Jinayah Perspective - Yusril Bariki (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The purpose of this research is to discuss juridical analysis of the decision of one of the Batang Religion court cases which will also be studied using the sociology of family law approach. There are two formulations of the problem in this study, first, how is marriage in Islamic law? Second, what is the analysis of the decision on case number 1864/Pdt.G/2022/PA.Btg in the study of the sociology of family law?. In normative juridical research with a qualitative approach, it has findings or results, namely that marriage has a very sacred purpose, especially in the marriage contract which is a great agreement (mitsaqan gholidan) which is solely to achieve the goal of Sakinah mawadah and wa Rahmah. The next consequence, in the sociological study of family law in looking at existing divorce decisions, is that normative law has a higher prescriptive level than sociological law, which has an empirical descriptive perspective. In contrast to the jurisprudential model which focuses more on results or political regulations, the sociological model of law focuses more on social structure. Dalam tujuan penelitian ini akan membahas mengenai analisis yuridis dalam putusan salah satu perkara pengadilan Agama Batang yang mana nanti akan dikaji juga dengan pendekatan sosiologi hukum dan fiqh jinayah. Rumusan masalah dalam penelitian ini ada dua, pertama, bagaimana pernikahan dalam hukum Islam. Kedua, bagaimana analisis putusan perkara nomor 1864/Pdt.G/2022/PA.Btg dalam kajian sosiologi hukum keluarga. Dalam penelitian yuridis normative dengan pendekatan kualitatif ini memiliki temuan ataupun hasil yaitu dalam pernikahan memiliki tujuan yang sangat sakral, terlebih didalam akad nikah merupakan sebuah perjanjian yang agung (mitsaqan gholidan) dimana semata-mata untuk menapai tujuan Sakinah mawadah dan wa Rahmah. Hasil berikutnya, dalamkajian sosiologi hukum keluarga dalam melihat putusan perceraian yang ada yakni Hukum normatif memiliki tingkat preskriptif yang lebih tinggi daripada hukum sosiologis, yang memiliki perspektif deskriptif empiris. Berbeda dengan model yurisprudensi yang lebih menitikberatkan pada hasil atau peraturan politik, model sosiologis hukum lebih menitikberatkan pada struktur sosial.